The Identification and Prioritization of the Professional Development Needs for Teachers of Career, Technical, and Agricultural subjects within Georgia Metropolitan Area School Systems - McAdoo, Charlie E., II (My University, 2018)
The purpose of this research study was to identify and prioritize the professional development needs for teachers of CTAE subjects within metropolitan Atlanta school systems. The methodology was primarily relational with descriptive components that relied on quantitative data. The administered survey called for participants to self-report demographic groups (i.e. Experience Level, School Type, and School Population). Secondly, participants completed online surveys yielding data that identified professional development needs relative to demographic variables. A modified Borich (1980) Needs Assessment Model was used to identify the perceived importance and perceived competency of 20 competencies prescribed by the Georgia Teacher Assessment of Performance Standards (TAPS). Once analyzed, the researcher identified and described professional development needs relative to demographic variables.
Chapter I: INTRODUCTION 1 -- Background 3 -- Theoretical Framework 5 -- Problem Statement 7 -- Purpose of the Study 7 -- Research Questions 7 -- Conceptual and Operational Definitions of Key Terms 8 -- Limitations of the Study 9 -- Significance of the Study 10 -- Chapter II: REVIEW OF THE LITERATURE 11 -- Professional Development 11 -- Accountability and Career and Technical Education 13 -- Needs Assessment for Program Improvement 14 -- Georgia Teacher Assessment of Performance Standards 15 -- Professional Development in Georgia 15 -- CTAE Professional Development in Georgia 17 -- CTAE Professional Development 17 -- Chapter III: METHODOLOGY 20 -- Introduction 20 -- Purpose of the Study 22 -- Research Questions 23 -- Population and Sample 25 -- Instrumentation 25 -- Procedure 29 -- Descriptive Statistics 30 -- Data Analysis 31 -- Limitations and Delimitations 32 -- Summary 33 -- Chapter IV: FINDINGS 35 -- Introduction 35 -- Review of the Research Questions 36 -- Population and Sample 36 -- Data Gathering and Data Analysis 37 -- Section One: Demographic Data Analysis 38 -- Number of CTAE Teachers by Experience Group 38 -- Number of CTAE Teachers by School Type 39 -- Number of CTAE Teachers by School Population 40 -- Section Two: Survey Results 40 -- All Demographic Variable Results 41 -- Section Two: Demographic Group Variable Group Analysis 45 -- Experience Results 45 -- Beginning Teacher 47 -- Mid Career Teachers 50 -- Veteran Teachers 54 -- Late Career Teachers 59 -- Comparison of Experience Variables 63 -- School Type Results 64 -- Comprehensive Secondary Setting 65 -- Career Academy 70 -- Middle School 75 -- High School 79 -- Comparison of School Types 84 -- School Population Results 85 -- Small School Setting 86 -- Medium School Setting 91 -- Large School Setting 95 -- Comparison of School Types 99 -- Overall Comparative Data Analysis 100 -- Chapter V: CONCLUSIONS AND RECOMMENDATIONS 102 -- Introduction 101 -- Research Questions 103 -- Conclusions 106 -- Recommendations for Professional Development 108 -- Experience Level Recommendations 109 -- School Type Recommendations 110 -- School Population Recommendations 112 -- Recommendations for Further Research 113 -- Limitations 115 -- Summary 116 -- References 117 -- Appendices 126 -- Appendix A: Email Requesting Permission to Conduct Study 126 -- Appendix B: Email Requesting MWDS Calculator 128 -- Appendix C: Email sent to teachers of CTAE subjects 131 -- Appendix D: Survey Instrument 133 -- Appendix E: VSU Institutional Review Board Approval 143 -- Appendix F: Atlanta Public School System Research Approval 145 -- Appendix G: City Schools of Decatur Research Approval 147 -- Appendix H: Dekalb County School System Research Approval 149 -- Appendix I: Douglas County School System Research Approval 151 -- Appendix J: Forsyth County School System Research Approval 153 -- Appendix K: Fulton County School System Research Approval 155 -- Appendix L: Marietta City School System Research Approval 157 -- Appendix M: Rockdale County School System Research Approval 159.
Keywords: Dissertations, Academic--United States; Career development; Organizational effectiveness--Management; Agricultural education; Teacher effectiveness